Systematic literature review on developing an integrated STEM leadership model for middle leaders in school - Saifulbahri, Abdul Rahman; Abdul Halim, Busari; Mohammad Nur Azhar, Mazlan; Adawati, Suhaili (Institute of Advanced Engineering and Science (IAES) in collaboration with Intelektual Pustaka Media Utama (IPMU), 2025)
This systematic literature review investigates the development of an integrated science, technology, engineering, and mathematics (STEM) leadership model tailored for middle leaders in Malaysian schools. The introduction highlights the global emphasis on STEM education to foster innovation and economic growth, while acknowledging Malaysia’s commitment to enhancing STEM capabilities within its educational system. The problem statement identifies a gap in effective STEM leadership among middle leaders, which is critical for implementing STEM initiatives and improving student outcomes. To achieve this, we conducted an extensive search of scholarly articles from reputable databases such as Scopus and Web of Science (WoS), focusing on studies published between 2021 and 2024. The flow of study is based on PRISMA framework. The database found (n=34) final primary data was analyzed. The finding was divided into three themes which are i) STEM education policy and implementation; ii) leadership in STEM educational; iii) professional development in STEM education. The conclusion emphasizes the need for a specialized leadership model that incorporates instructional leadership principles, fosters professional development, and supports collaborative practices among middle leaders. This integrated model aims to address the unique challenges faced by middle leaders in Malaysian schools, ultimately enhancing STEM education and contributing to Malaysia’s educational and economic aspirations.